Perception of former illegal logger to agroforestry in Tetelan land of Meru Betiri National Park, Indonesia - Khomsah, Khusnatul; Ihsannudin; Pinuji, Sukmo; Luthfiyah, Lennny (AGROMIX, 2025)
Introduction: A sustainable livelihood program for former illegal loggers implemented by agriculture cultivation in rehabilitation zones or â€œTetelanâ€ land. Then, the agroforestry system should be applied to restore the function of forests and generate economic value. The research aims to examine the perceptions of former illegal loggers and the factors that influence the application of agroforestry on â€œtetelanâ€ land. Methods: The research was conducted in Sanenrejo Village and Andongrejo Village, Tempurejo District, Jember Regency, East Java as buffer villages of the Meru Betiri National Park (MBNP). The research data used has cross-sectional characteristics. The data were measured using the Likert scale and analyzed using descriptive quantitative methods, followed by the Chi-square method to determine the effect of the relationship between variables. Results: Perception of former illegal loggers of agroforestry in â€œtetelanâ€ land is in a good category. This means that efforts to implement an agroforestry system in "Tetelan" land to restore forest function have a high chance of success. At the same time, the factors that significantly influence the application of agroforestry are education and income. Conclusion: Individual approach efforts should target ex-illegal logger farmers with an elementary school education and low income (between IDR 300,000â€“IDR 6,200,000).